HIV Capsid Protein Genetic Diversity Across HIV-1 Variants and Impact on New Capsid-Inhibitor Lenacapavir - Troyano-Hernáez, Paloma; Reinosa, Roberto; Holguín, África (Frontiers in Microbiology, 2022)
HIV p24 capsid protein has an essential structural and functional role in the viral replication cycle, being an interesting target for vaccine design, diagnostic tests, and new antiretroviral drugs. HIV-1 variability poses a challenge for the accuracy and efficiency of diagnostic and treatment tools. This study analyzes p24 diversity among HIV-1 variants and within its secondary structure in HIV-1 M, O, P, and N groups. All available HIV-1 p24 nucleotide sequences were downloaded from the US Los-Alamos-HIV-Sequence-Database (LANL), selecting 23,671 sequences belonging to groups O, N, P, and M (9 subtypes, 7 sub-subtypes, and 109 circulating recombinant forms or CRF). Using a bioinformatics tool developed in our laboratory (EpiMolBio program), we analyzed the amino acid conservation compared to HXB2 subtype B reference sequence and the V-markers, or amino acid changes that were specific for each variant with at least 10 available sequences. We inferred the p24 consensus sequence for HIV-1 and for each group to analyze the overall conservation in p24 main structural regions, reporting the rate of substitutions per variant affecting the capsid assembly and molecule-binding, including those associated with resistance to the new capsid-inhibitor lenacapavir and the key residues involved in lenacapavir-p24 interaction, according to the bibliography. Although the overall structure of p24 was highly conserved, the conservation in the secondary structure varied between HIV-1 variants and the type of secondary structure. All HIV-1 variants presented >80% amino acid conservation vs. HXB2 reference sequence, except for group M sub-subtype F1 (69.27%). Mutants affecting the capsid assembly or lenacapavir capsid-binding were found in <1% of p24 consensus sequence. Our study reports the HIV-1 variants carrying 14 unique single V-markers in 9/38 group M variants and the rate of p24 conservation in each secondary structure region among the 4 HIV-1 groups and group M variants, revealing no natural resistance to lenacapavir in any HIV-1 variant. We present a thorough analysis of p24 variability among all HIV-1 variants circulating to date. Since p24 genetic variability can impact the viral replication cycle and the efficacy of new p24-based diagnostic, therapeutic, and vaccine strategies, conservation studies must consider all HIV-1 variants circulating worldwide.